EFEKTIVITAS CORE STABILITY TRAINING TERHADAP PENCEGAHAN PRIMER DAN SEKUNDER LOW BACK PAIN - Davina Syla Quishalana; Tubagus Fauzan Wahyu Fadilah; Nuryani Sidarta; Mitchel Mitchel; karina sylvana Gani; Erica Kholinne (Fakultas Kedokteran Universitas Trisakti, 2026)
Low back pain is a common musculoskeletal disorder that has a significant impact on physical function, work productivity, and quality of life. The majority of low back pain cases are classified as non-specific and are associated with impaired neuromuscular control and segmental instability of the lumbar spine. Core stability training is a conservative exercise approach that focuses on the activation and strengthening of deep trunk muscles to enhance lumbopelvic stability and reduce mechanical stress on passive spinal structures. This review article aimed to evaluate the effectiveness of core stability training in the prevention of low back pain related to physical activity. The article was developed through a review of experimental studies, randomized controlled trials, and meta-analyses that assessed the effects of core stability training on postural stability, neuromuscular control, trunk muscle strength and endurance, as well as the incidence and recurrence of low back pain. The findings indicated that core stability training improved functional spinal stability, enhanced neuromuscular coordination, and reduced the risk of low back pain as both a primary and secondary preventive intervention. Given its safety and ease of implementation, core stability training can be recommended as an effective preventive strategy.